2018
DOI: 10.1038/hgv.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Novel compound heterozygous variants in the LARP7 gene in a patient with Alazami syndrome

Abstract: The LARP7 gene encodes a chaperone protein of the noncoding RNA 75 K, and mutations in this gene have been identified in patients with Alazami syndrome. Herein, we report another Japanese patient with Alazami syndrome and novel compound heterozygous variants in LARP7 (i.e., c.370delG, p.Glu124fs*38 and c.641_667+25del involving the splice donor site of intron 8). These findings provide further evidence that biallelic LARP7 defects cause the phenotype of Alazami syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…The mutational mechanism is loss-of-function presumably due tononsense-mediated mRNA decay [1,5] [3,5]. Our patient's fi nal adult height is not as signifi cantly impaired as the initial case descriptions [2,3,6] and not in the range typical for primordial dwarfi sm, and more in accordance with the growth reported byHollink et al, [1] and Dateki et al [5].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The mutational mechanism is loss-of-function presumably due tononsense-mediated mRNA decay [1,5] [3,5]. Our patient's fi nal adult height is not as signifi cantly impaired as the initial case descriptions [2,3,6] and not in the range typical for primordial dwarfi sm, and more in accordance with the growth reported byHollink et al, [1] and Dateki et al [5].…”
Section: Discussionsupporting
confidence: 90%
“…Hollink et al, [1], reported two unrelated Alazami syndrome patients with homozygous loss-of-function variants in LARP7. Dateki et al, [5], reported another patient with Alazami syndrome having unique compound heterozygous mutations in LARP7 [5]. Recently Imbert-Bouteille M et al, [6], with other previously reported Alazami syndrome patients to portray further phenotypic manifestations related to this syndrome.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We describe a male infant who, at 17 months of age, is the youngest patient diagnosed with Alazami syndrome to date. He is also the first reported patient with an intronic variant predicted to cause abnormal splicing, as the variants previously‐reported in the literature are frameshift variants resulting in a prematurely truncated protein (Alazami et al, ; Dateki et al, ; Hollink et al, ; Holohan et al, ; Imbert‐Bouteille et al, ; Ling & Sorrentino, ). His physical development appears consistent with previous reports of Alazami syndrome, with short stature and characteristic facial features noted in addition to other features particular to Alazami syndrome such as overlapping toes and rough skin over his feet.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, only one patient is reported to have meaningful speech (Hollink et al, ), though these details are not consistently provided, and the younger patients reported may have yet to develop additional language skills. These individuals also share a unique facial gestalt with the initial family described and are all reported to have pathogenic protein‐truncating variants in LARP7 (Dateki et al, ; Hollink et al, ; Holohan et al, ; Imbert‐Bouteille et al, ; Ling & Sorrentino, ). The age at diagnosis ranges from 2 to 26 years of age and many families are reported to be consanguineous (Dateki et al, ; Hollink et al, ; Holohan et al, ; Imbert‐Bouteille et al, ; Ling & Sorrentino, ).…”
Section: Introductionmentioning
confidence: 97%